Semantic Study of Boat Maker Jargon: Basis for an Industrial Arts English Lesson Exemplar - Glenvi L. Amores; Verdemerl S. Bacay; Karylle Joy M. Cañete; Key T. Villalon; Ruel T. Bonganciso (Research Synergy Foundation Press, 2024)
Panday, the Filipino term for carpenter, has a unique language of its own, filled with specialized jargon that is integral to the craft. Despite the significance of panday jargons in the Filipino boat-making culture, very few know the semantic functions of these terminologies. This study aims to compile these boat-maker jargons and determine their semantics as to how they are used in the field of work. Because the study focuses on the use of language in different cultural groups, particularly boat makers, ethnolinguistic design was used. This study employed convenience sampling, with researchers selecting participants with at least 10 years of experience as boat makers. Responses were analyzed using thematic analysis and jargon-filtered before they were categorized using a matrix. Accordingly, the study determined the jargon used in materials, equipment, tools, wooden boat parts, and processes. The data also showed additional jargon that were not categorized yet are essential in the field of boat making, such as inadlaw, pakyaw, master, and helper. These jargons created concepts encompassing the boat-making culture. This included the apprenticeship that determined the master and the helper and labor agreements, such as inadlaw and pakyaw. This daily routine of labor exposes workers to tools, thus affecting their routine if not brought. The participants’ statements proved that their job has had a meaningful impact on their lives since they started it. Further research exploring topics in similar fields is recommended to examine the distinctions between jargon in different geographical and cultural contexts.